Maintenance Theory of Reliability - Nakagawa, Toshio (Springer Series in Reliability Engineering,, 2005)
The maintenance of systems in engineering is of increasing concern to managers and designers in all branches of engineering, whether they are producing high-quality products or designing highly-reliable systems. In recent decades, reliability theory has produced many innovations in maintenance policy. Maintenance Theory of Reliability is a survey of useful and practical maintenance models covering replacement, preventive maintenance and inspection. The book provides a detailed introduction to maintenance policies, updates the reader on the current status of the field and indicates future directions. The reader will learn the theory of maintenance and how to apply models in practice. The book will serve as an essential reference for graduate students and researchers in reliability theory and a useful guide for reliability engineers engaged in maintenance work. The Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government. .